Results 1 to 4 of 4

- Mar 10th 2010, 10:58 PM #1

- Joined
- Nov 2009
- Posts
- 42

## [SOLVED] w= θ/t

it's..

w = θ/t

wt = (θ/t)t

wt = θ

wt/w = θ/w

t = θ/w

why isn't it...

w= θ/t

(w=θ/t) x 1/θ

w/θ = 1/t

(w/θ= 1/t) x t

t x w/θ = 1

t = 1/ (w/θ)

that's what i calculated........... can someone tell me what i did wrong?

i know the top one is right.. i just tried to do it a different way and it just went horribly wrong.

- Mar 10th 2010, 11:07 PM #2

- Joined
- Dec 2009
- From
- 1111
- Posts
- 872
- Thanks
- 3

- Mar 10th 2010, 11:37 PM #3

- Joined
- Nov 2009
- Posts
- 42

- Mar 11th 2010, 12:26 AM #4

- Joined
- Dec 2009
- From
- 1111
- Posts
- 872
- Thanks
- 3